FIRE RESISTANCE MEASUREMENT OF OIL PALM EMPTY FRUIT BUNCH-PLASTIC COMPOSITES BY COMBUSTIBILITY TEST - Wahyu Dwianto; Myrtha Karina (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2008)
FIRE RESISTANCE MEASUREMENT OF OIL PALM EMPTY FRUIT BUNCH-PLASTIC COMPOSITES BY COMBUSTIBILITY TEST. This paper reports combustibility test of Oil Palm empty fruit bunch (EFB)-plastic composites to determine their fire resistance. Specimens were of several composite types with dimension of 40 x 40 x 50 mm3. Combustibility test was done according to JIS A 1321-1975 by using small scale cylindrical furnace. Initial temperature of furnace was set at 750 ºC ± 1 ºC. Based on JISA1321-1975, all the composites tested were classified into combustible materials due to their temperature gradient higher than 50 ºC. The lowest temperature gradient was attained at 75 ºC for PE-EFB/GF/GF short fibers composite. However, the result showed that the temperature gradient of PE-EFB/GF/GF short fibers composite was lower compared to some solid woods and commercial wood-based panels. Weight loss has a strong relationships with density of the composites, shown by polynomial equation y = -181.82 x2 + 452.36 x - 205.5, R2 = 0.9156. The density of composites which formed EFB layers tended to decrease, conscequently increased their weight loss. Concerning the both factors, PE-EFB/GF/GF short fibers composite was recommended as the best fire resistance among the tested composites due to its lowest temperature gradient (75 ºC) and relatively lower weight loss (64.17 %).